The effect of osteochondral lesion size and ankle joint position on cartilage behavior: numerical and in vitro experimental results - Ramos, A. (2025)
Osteochondral lesion of the talus is defined as damage in the cartilage that covers the talus bone, compromising the integrity of the joint in the long term. Due to the low incidence of this pathology, there are few studies to understand the importance of lesion size and position in cartilage strains. The purpose of this study is then to analyze the influence of the lesion size in joint behavior. A 3D virtual and in vitro model of a patient’s injured ankle joint was developed. The models were built using CT scan and MRI images, to obtain the CAD models of intact and with 10 mm lesion size for 3D print models using additive manufacturing. The physical model was tested with 685N applied vertically to determine experimentally the principal strains and contact pressures in the cartilage. Five finite element models were developed with lesion dimensions (5 to 20 mm) and with 3 ankle joint positions. The numerical and experimental results were correlated with an R2 =0.86 justified by the complexity of the model geometry. The maximum principal strain was 2566με in the plantar flexion position without lesion. The experimental contact area between cartilages increased by 1.2% in the 10 mm lesion size for 431 mm2. The maximum stress in the cartilage was observed for a 20 mm lesion size with 2.5 MPa. The 5 and 10 mm sizes present similar results; the 15 mm lesion size presents a stress increase of 13% comparatively with 10 mm. Plantar flexion seems to be the most critical configuration; stress increases with an increase of lesion size around the cartilage.